Numerical Study of Nano Enhanced PCM Incorporated Heat Sink with Wavy Shaped Plate Fins - Hazra, Soumik Kumar (Universitas Mercu Buana, 2026)
Modern high-power electronic devices require efficient passive cooling strategies to maintain safe operating temperatures. This study presents a two-dimensional numerical investigation of a nano-enhanced phase change material (NePCM)-based heat sink incorporating wavy-shaped plate fins. The NePCM consists of paraffin with 3 wt% CuO nanoparticles to enhance thermal conductivity. The novelty of this work lies in the integration of wavy-shaped fins to promote natural convection and accelerate PCM melting, thereby improving heat dissipation performance. The governing continuity, momentum, and energy equations are solved using the enthalpy–porosity method under a constant heat flux of 10,000 W/m² and a convective boundary condition of 10 W·m⁻²·K⁻¹. Parametric analyses are conducted by varying the number of cavities (3, 5, and 7) and fin height (40–50 mm). The results show that the NePCM heat sink reduces the peak temperature from 438 K (conventional) to 381 K, corresponding to a reduction of approximately 13% after 30 minutes. The wavy fin configuration enhances fluid circulation within the molten PCM, leading to faster melting and improved heat absorption. Increasing cavity number from 3 to 7 reduces the average temperature by up to 7 K, while increasing fin height to 50 mm further lowers the temperature by approximately 10–20 K compared to shorter fins. The combined effect of latent heat storage and enhanced natural convection induced by wavy fins significantly improves thermal management performance, making the proposed design a promising solution for compact electronic cooling applications.